Comparative efficacy of pharmacological agents on abdominal aortic aneurysm growth rate: a systematic review and network meta-analysis - Wen, Cheng; Li, Lilong; Wang, Bo; Xie, Linyang; Wu, Huaping (Frontiers in Pharmacology, 2026)
BackgroundAbdominal aortic aneurysm (AAA) progression lacks proven medications. This study aimed to indirectly compare common drugs’ effects on AAA growth rate using a network meta-analysis (NMA) of randomized controlled trials (RCTs) and cohort studies, assessing the reliability of evidence.MethodsWe systematically searched the Cochrane Library, Embase, Web of Science, and PubMed until 5 June 2025. A Bayesian NMA synthesized direct and indirect evidence on drug effects on AAA growth rate, using standardized mean differences (SMD) with credible intervals (CrI). Cohort study results were analyzed separately.ResultsAfter screening, 11 RCTs (2,135 subjects) and 13 cohort studies were included. Pooled RCT results showed roxithromycin significantly reduced AAA growth (SMD [95% CrI]: 0.39 [-0.69 to −0.10]). Roxithromycin also demonstrated advantages over amlodipine and doxycycline in indirect comparisons. Propranolol, perindopril, metformin, azithromycin, and ticagrelor showed no significant benefits. Cohort studies linked slower growth to statins and glucose-lowering drugs (insulin, metformin).ConclusionRoxithromycin, statins, and metformin show promise for potentially limiting AAA expansion. However, findings are constrained by methodological limitations (study design, sample size), necessitating future validation via high-quality RCTs.